2016
DOI: 10.1101/096958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Canonical and cross-reactive binding of NK cell inhibitory receptors to HLA-C allotypes is dictated by peptides bound to HLA-C

Abstract: Background. Human natural killer (NK) cell activity is regulated by a family of killer-cell Ig-like receptors (KIR) that bind human leucocyte antigen (HLA) class I. Combinations of KIR and HLA genotypes are associated with disease, including susceptibility to viral infection and disorders of pregnancy. KIR2DL1 binds HLA-C alleles of group C2 (Lys 80 ) and KIR2DL2 and KIR2DL3 bind

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 58 publications
(104 reference statements)
4
47
1
Order By: Relevance
“…6 Malcolm Sim showed that KIR2DL3 binding to HLA-C1 was more peptide-dependent than KIR2DL1 binding to C2, providing a possible explanation for why KIR2DL3-C1 interactions appear weaker than KIR2DL1-C2 interactions. 7 The peptide selectivity of KIR2DL3-C1 interactions may be important in cancer cell recognition because the peptides in the cancer cell may differ from those that shape NK cell education in resting state.…”
Section: Kir Structure and Peptidesmentioning
confidence: 99%
“…6 Malcolm Sim showed that KIR2DL3 binding to HLA-C1 was more peptide-dependent than KIR2DL1 binding to C2, providing a possible explanation for why KIR2DL3-C1 interactions appear weaker than KIR2DL1-C2 interactions. 7 The peptide selectivity of KIR2DL3-C1 interactions may be important in cancer cell recognition because the peptides in the cancer cell may differ from those that shape NK cell education in resting state.…”
Section: Kir Structure and Peptidesmentioning
confidence: 99%
“…KIR2DL2 and KIR2DL3 are inhibitory KIRs with a predominant specificity for the group 1 HLA-C allotypes (HLA-C1). Both these inhibitory receptors have similar specificities for peptide:MHC, as could be predicted from the high sequence homology of their extra-cellular domains (10).…”
mentioning
confidence: 87%
“…Binding of activating KIRs to HLA class I is influenced by HLA-bound peptides. [4][5][6] Since ERAP1 is primarily a MHC-I cargo optimizer, one could hypothesize that a 'slower' allele limits optimal peptide cargo, allowing for less optimal peptides to be bound and presented, eliciting cytotoxic responses. KIR2DS1 might enable NK cells to kill effectors of AD independently of ERAP1-provided peptide, whereas, in the absence of this KIR, the activity of CD8 + T cells contributing to AD might be influenced by an HLA-C*05:01presented peptide produced by ERAP1 more or less efficiently depending on its rs26618 variant.…”
Section: Discussionmentioning
confidence: 99%
“…3 NK cell function has been found to be affected by HLA class I-bound peptides. [4][5][6] The repertoire of these peptides is dependent on the activity of endoplasmic reticulum aminopeptidases 1 and 2 (ERAP1 and 2), which are polymorphic elements of antigen-presenting machinery. [7][8][9] Therefore, we examined several single nucleotide polymorphisms (SNPs) of the ERAP1 and ERAP2 genes, potentially affecting enzyme activity or expression 10 in patients with AD and healthy control individuals.…”
Section: Introductionmentioning
confidence: 99%